2018
DOI: 10.1038/s41419-018-1210-9
|View full text |Cite
|
Sign up to set email alerts
|

Long noncoding RNA ATB promotes the epithelial−mesenchymal transition by upregulating the miR-200c/Twist1 axe and predicts poor prognosis in breast cancer

Abstract: Recent studies indicate that the long noncoding RNA ATB (lncATB) can induce the epithelial−mesenchymal transition (EMT) in cancer cells, but the specific cellular targets of lncATB require further investigation. In the present study, the upregulation of lncATB in breast cancer cells was validated in a TGF-β-induced EMT model. Gain- and loss-of-function studies demonstrated that lncATB enhanced cell migration, invasion and clonogenicity in vitro and in vivo. LncATB promoted the EMT by acting as a sponge for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(51 citation statements)
references
References 42 publications
(60 reference statements)
1
46
0
Order By: Relevance
“…Increasing studies show that lncRNAs could be competing endogenous RNAs (ceRNAs) for miRNAs (Cui et al, ; Li et al, ). Hence, we speculated whether LOC105369748 could be a ceRNA for specific miRNAs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Increasing studies show that lncRNAs could be competing endogenous RNAs (ceRNAs) for miRNAs (Cui et al, ; Li et al, ). Hence, we speculated whether LOC105369748 could be a ceRNA for specific miRNAs.…”
Section: Resultsmentioning
confidence: 99%
“…Total protein was isolated from cultured cell lines using the radioimmunoprecipitation (RIPA) buffer (Cell Signaling Technology, Inc., Danvers, MA). Western blot analysis was performed according to the previous study (Li et al, ). The primary antibodies are as follows: anti‐E‐cadherin (1:2,000; cat.…”
Section: Methodsmentioning
confidence: 99%
“…Another identified lncRNA, PPP1R26-AS1, is reported in association with breast cancer in GWAS using the Gene Expression Omnibus (GEO) and Cancer Genome Atlas (TCGA) databases (Xu et al, 2017). Moreover, PPP1R26-AS1 and some other lncRNAs have been shown to be associated with luminal B subtypes of breast cancer (Xu et al, 2017;Li et al, 2018). Interestingly, the proteincoding partner of PPP1R26-AS1 lncRNA, PPP1R26, was also differentially expressed in all sets of neuroblastoma, which could shed light on the molecular function of the identified lncRNA.…”
Section: Discussionmentioning
confidence: 99%
“…Our group has previously reported that circulating lncRNAs act as potential novel biomarkers for diagnosis and prognosis of non‐small cell lung cancer . Several recent studies have focused on the involvement of lncRNAs in tumor metastasis because these lncRNAs have shown great promise in the discovery of new biomarkers for predicting prognosis in individual patients . Some lncRNAs, such as HCP5, CAR10, NEAT1 and MALAT1, promote lung cancer metastasis via various mechanisms .…”
Section: Introductionmentioning
confidence: 99%
“…10 Several recent studies have focused on the involvement of lncRNAs in tumor metastasis because these lncRNAs have shown great promise in the discovery of new biomarkers for predicting prognosis in individual patients. [11][12][13] Some lncRNAs, such as HCP5, CAR10, NEAT1 and MALAT1, promote lung cancer metastasis via various mechanisms. 7,14,15 These findings suggest that the tumor metastasis-associated lncRNAs in lung cancer have potential prognostic implications.…”
Section: Introductionmentioning
confidence: 99%